Effectiveness of guiding instrument replacement In tubary reanastomosis by minilaparotomy (Research, Society and Development, 2021)
To evaluate the effectiveness of using a lower cost guide instrument in the surgical technique of tubal reanastomosis performed in women with female infertility due to an obstructive factor from previous tubal ligation. Data were collected from medical records of couples from the Human Reproduction Service of a public teaching hospital in Teresina – Piauí with secondary sterility who underwent reanastomosis by the modified technique from January 2008 to December 2018. Socioeconomic and demographic variables, clinical background were evaluated. gynecological, motivations, procedure data and results obtained with the procedure, the outcome being the registration of tubal patency by hysterosalpingography or pregnancy in the postoperative follow-up. In the profile of the studied population, there was a predominance of self-reported brown skin color patients, with elementary education, without paid occupation and with a mean age of 33±2.9 years. Most would have opted for tubal ligation by their own decision (53%), while the presence of a new partner was the reason raised for seeking to reverse sterilization (72%). Considering the success of recanalization, uni or bilateral, and evaluating factors that could be related to higher percentages of positive outcomes, significance was observed with p